GOVERNMENT FUNDING INTERVENTION AND SUSTAINABLE OPERATIONS OF MICRO, SMALL AND MEDIUM ENTERPRISES IN NIGERIA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
This paper investigated the effect of government financial intervention on the operations of the Micro, Small and Medium Enterprises (MSMEs) in Nigeria. Based on contextual analysis on relevant academic studies.  The micro, small, medium enterprises (MSMEs) sector of the Nigerian economy, as discovered from the study, has been performing strategic role in promoting the economy: in encouraging start ups and entrepreneurial development; has a high capacity in providing employment for the teeming population of youths; contributing substantially to the country’s export drive, poverty alleviation, gross domestic product (GDP), growth and development, and utilization of the available productive resources. Furthermore, this subsector of the economy is recognized for workforce employment, income generation and development of both technical and entrepreneurial skills, which is well documented in empirical literature, and will continue to be of great significance to the economy (Abu, 2024). In recognition of these inherent benefits of MSMEs to the economy, there have been some financial supports accorded by the government to the sector, among which are the CBN MSMEs Fund and TraderMonie. However, the study revealed that such financial supports have not made appreciable impact on their sustainable operations due to some intractable factors. Hence, this paper recommends that there is the pressing need to refocus the government financial support for these vital enterprises, such as equipment financing to obviate funds diversion while they fund their working capital through financial bootstrapping. Such approach is considered imperative towards ensuring the sustainable operations of the MSMEs for their robust contribution to the nation’s economic growth and development.